2019
DOI: 10.1080/14760584.2019.1692657
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal delivery of tuberculosis vaccines: a review of current approaches and challenges

Abstract: Introduction: Tuberculosis (TB) remains a major health threat and it is now clear that the current vaccine, BCG, is unable to arrest the global TB epidemic. A new vaccine is needed to either replace or boost BCG so that a better level of protection could be achieved. The route of entry of Mycobacterium tuberculosis, the causative organism, is via inhalation making TB primarily a respiratory disease. There is therefore good reason to hypothesize that a mucosally delivered vaccine against TB could be more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 150 publications
4
34
0
Order By: Relevance
“…Previous findings demonstrated the safety of this approach and showed that the pulmonary route was as efficacious as the subcutaneous route [16]. The pulmonary administration of DNA vaccines is being examined for various infections, including influenza, measles, and tuberculosis [17]. However, to the best of our knowledge, limited information is currently available on the pulmonary administration of DNA vaccines for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings demonstrated the safety of this approach and showed that the pulmonary route was as efficacious as the subcutaneous route [16]. The pulmonary administration of DNA vaccines is being examined for various infections, including influenza, measles, and tuberculosis [17]. However, to the best of our knowledge, limited information is currently available on the pulmonary administration of DNA vaccines for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The total mucosal surface area is about 200 times larger than skin, and vaccination at the sites of pathogen invasion could generate a protective immunological response [46]. While oral BCG was the initial delivery method almost a century ago, oral vaccines generally must survive the acidic environment of the stomach and run the risk of generating tolerance without an adjuvant [47]. That said, comparing intradermal and oral delivery in humans, oral BCG induced stronger mucosal responses, as measured by Mtb-specific bronchoalveolar lavage (BAL) T-cells and secretory Immunoglobulin A (IgA), though intradermal BCG resulted in stronger systemic Th1 responses [48].…”
Section: Vaccine Deliverymentioning
confidence: 99%
“…Animal studies have also provided important insights into the relevant delivery routes of TB vaccines. The standard routes of immunization in mammals and humans include intradermal and intramuscular, which aim to elicit systemic immune responses (Stylianou et al, 2019;Dijkman et al, 2019;Brandt et al, 2004;Skeiky et al, 2004). However, in 1973, a study in NHPs showed that Diedrich et al, 2010;Lin et al, 2009;Capuano et al, 2003Cooper, 2014Medina andNorth, 1998 Peng et al, 2015;Kesavan et al, 2009;Manabe et al, 2008;Manabe et al, 2003Clark et al, 2014Grover et al, 2012;Williams et al, 2009Pesciaroli et al, 2014Villarreal-Ramos et al, 2014;Cassidy, 2006;Buddle et al, 1999Parikka et al, 2012Swaim et al, 2006;Davis et al, 2002 mucosal vaccination could enhance protection against airborne Mtb (Barclay et al, 1973).…”
Section: Mammalian Models In Preclinical Evaluation Of Tb Vaccinesmentioning
confidence: 99%
“…Animal studies have also provided important insights into the relevant delivery routes of TB vaccines. The standard routes of immunization in mammals and humans include intradermal and intramuscular, which aim to elicit systemic immune responses ( Stylianou et al, 2019 ; Dijkman et al, 2019 ; Brandt et al, 2004 ; Skeiky et al, 2004 ). However, in 1973, a study in NHPs showed that mucosal vaccination could enhance protection against airborne Mtb ( Barclay et al, 1973 ).…”
Section: Mammalian Models Of Tbmentioning
confidence: 99%